The Analysis of School Strategy in the Development of Natural Intelligence for Kindergaten Children - Naila Fikrina Afrih Lia; Roinah Roinah; Muhamad Rusadi Letasado; Eva Solina Gulton; Harizahayu Harizahayu (Journal on Education, 2023)
In order to prepare learning that can enhance children's naturalist intelligence, learning methodologies are being examined and described in this study. Descriptive data are employed in the research method, which is a qualitative one. Seven classroom teachers and one school principals or deputy principals served as the study's subjects. Data collection, data reduction, data presentation, and verification or conclusions were all processes in the Miles Huberman analysis of the data. This study found the diversity of strategies applied in preschool, namely by using or applying three stages of strategy in the learning process, namely: first, the planning strategy, which includes the following things: learning objectives, planning indicators to achieve naturalist intelligence, learning program planning, approach planning, methods and techniques, and learning tactics. Second, the implementation strategy stage includes strategies to manage content and learning material, send content and learning material through the media, and manage learning activities. Third, the assessment strategy stage, which includes the assessment of child development and the teacher's teaching ability in the development of the child's naturalist intelligence